USB movable memory with safety encryption function - LIUJIA XU (2006)
The utility model relates to a USB movable memory with a safety encryption function, which comprises a memory unit used for memorizing data, an encrypted unit used for realizing the secure logon of the plugged computer and encrypting the document in the computer, and a built-in CPU unit used for controlling the data storage and transmission of the memory unit and the encryption of the encrypted unit, wherein the built-in CPU unit is connected with the memory unit and the encrypted unit through a control bus, and the movable memory conforms to the general USB transfer protocol and the plug and play specification. By adopting the utility model, the secure logon of the plugged computer can be carried out, the document in the computer can be encrypted, and the accessible sharing resource of the computer can also be encrypted.